(untitled) (Journal of the Management Sciences, 2023)
The study examines the effect of tax audit and investigations strategies on direct tax payment method as a tax revenue collection method in Nigeria, which is the main objective of the study. Descriptive survey research design was adopted in obtaining data based on the opinion of respondents from the Federal Inland Revenue service (FIRS) in Nigeria. The population of the study was 350 staff of FIRS selected from five states in south eastern Nigeria (70 per state), who were administered with a questionnaire. The study made use of convenience sampling technique out of which 250 questionnaire filled by the staff was adopted as the study sample size. The study employed descriptive statistics such as percentages and frequencies and the use of linear regression method. Three elements of tax audit and investigation (RKO, IOCRB, and PATC) were found to have significant effect on direct tax payment [DT] P with P-value that is less than 0.05. ATR, IOCRB, PATC, and SNC have negative effects while RKO and ATPIS were positively related to DTP. From the results, ATR has a coefficient of -0.022461, showing that a one unit increase (decrease) in ATR will lead to about 0.022 unit decrease (increase) in DTP. This is consistent with apriori expectation that increase ATR will increase direct tax payment. This also indicates that a proportionately change in DTP is less than a proportional increase (decrease) in ATR. In the same vein, IOCRB with a coefficient of -0.091019, shows that a one unit decrease (increase) in IOCRB results to about 0.09 unit increase (decrease) in DTP. This is in line with aprori expectation that increase in IOCRB has increased enforcement of administrations legal mandate on tax revenue collection, post introduction of Tax audit and Investigations. Coefficient of -0.091019 for PATC shows that a one unit increase (decrease) in PATC results to about 0.091 unit decrease (increase) in DTP. This is at variance with the apriori expectations. It equally indicates a proportional change in DTP is inelastically related to IOCRB. Similarly, sanction for non-compliance (SNC), has a coefficient of -0.019184, indicating that a one unit increase (decrease) in SNC results to about 0.019 unit increase (decrease) in DTP, This means that DTP is inelastically related to SNC. A positive coefficient of 0.117037 and 0.056739 reported for RKO and ATPIS respectively, indicate that a unit increase (decrease) in the two independent variables will respectively lead to 0.11 and 0.056 increase (decrease) in DTP. There results satisfied economic apriori expectation that RKO and ATPIS are likely to increase DTP. Proportionally, changes in DTP are inelastic with respect to changes in both RKO and ATPIS. However, ATR, ATPIS and SNC were found to have insignificant effect on DTP with P-values that are in excess of our chosen alpha level of 0.05. ATR and SNC were negatively correlated with DTP while ATPIS was positively related with DTP. ATPIS has a coefficient of 0.056736, this shows that one unit increase or decrease in ATPIS will lead to about 0.06 unit increase or decrease in DTP. The responsiveness of DTP to change in ATPIS is inelastic and infinitesimal. The following findings were arrived at through the test of the research hypotheses earlier formulated in this study. Taxpayer’s record keeping obligation has an insignificant effect on direct tax payment in Nigeria. While, access to taxpayers’ books and records has a significant effect on direct tax payment in Nigeria. Furthermore, access to third party information source has an insignificant effect on direct tax payment in Nigeria. While, access to information from other countries revenue authorities has a significant effect on direct tax payment in Nigeria. Again, powers to amend returns from tax payers claim has a significant effect on direct tax payment in Nigeria. Lastly, sanctions for non compliance have an insignificant effect on direct tax payment in Nigeria. It is recommended that the ongoing propagation of digital taxation by scholars should be explored as a possible means to create a digital medium through which tax automations can be enhanced in Nigeria. Tax automated channels if included at corporate and individual level will enhance direct tax payment strategy. Also, through such automated channels, tax audit and investigation processes like information gathering will greatly improve.